2021
DOI: 10.1186/s13098-021-00737-1
|View full text |Cite
|
Sign up to set email alerts
|

The association of sleep duration and metabolic syndrome in the Bandare-Kong cohort study, a cross-sectional survey (finding from PERSIAN cohort study)

Abstract: Background A variety of health problems, such as metabolic syndrome (MetS), have been linked to sleep disorders. While numerous epidemiological studies have shown a U-shaped relationship between sleep duration and poor health outcomes, the results were limited and inconsistent. This study was designed to evaluate the relationship between sleep duration and MetS. Methods This population-based study was conducted on the participants aged 35–70 of Ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…These findings are consistent with previously published research literature. [19][20][21] A meta-analysis by Che et al found that beginning from 7-8 hours of sleep, for every hour reduction in sleep duration, the risk of metabolic syndrome increases by 8%. 22 Although the biological basis is still unknown, there are multiple putative immunologic, endocrinologic, and metabolic processes proposed to explain the associations between MetS and lower sleeping durations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with previously published research literature. [19][20][21] A meta-analysis by Che et al found that beginning from 7-8 hours of sleep, for every hour reduction in sleep duration, the risk of metabolic syndrome increases by 8%. 22 Although the biological basis is still unknown, there are multiple putative immunologic, endocrinologic, and metabolic processes proposed to explain the associations between MetS and lower sleeping durations.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 23 , 24 According to Iftikhar et al, when sleep is restricted, the levels of ghrelin rise while leptin levels drop which leads to increased hunger especially for fatty and starchy food as these increase the activity of the neuronal reward pathways. 21 These hormonal fluctuations could result in an increase in BMI. Another possible explanation for the association between BMI and short sleep duration is mechanical obstruction caused by fat around the neck.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop effective prevention programs, several cohort studies have been conducted to better understand the risk factors for MetS and examine MetS components [ 23 25 ], yet this prior research has limitations including relatively short follow-up times (one to four years) [ 26 ], variation in diagnostic criteria for MetS, or studies on populations of different ethnicities, which may affect generalisability to the Indonesian context [ 27 , 28 ]. Another study also explored MetS incidence using a similar six-year cohort, but did not rigorously select participants based on complete MetS component profiles and medication usage, which could introduce bias [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have already demonstrated that, in children, adolescents, and adults, the length of sleep is a significant risk factor for developing hypertension and other cardiometabolic illnesses [11][12][13]. However, several in-depth investigations using objective sleep measurement techniques, such as polysomnography, found no link between senior people's high blood pressure and their short sleep duration [14][15][16]. In this systematic review study, we discuss the previously reported relation between hypertension and sleeping duration in previously published studies in the database.…”
Section: Introductionmentioning
confidence: 99%